Rapsódia no pantanal - Nascimento, Edna Maria Fernandes dos Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
O artigo propõe mostrar, a partir da leitura do texto “Ao Pantanal”, de Guimarães Rosa, como a presença desta região brasileira impregna o narradorprotagonista que relata a “rapsódia de percepções” que vivenciou quando da suatravessia. A concretude e condensação da linguagem inscrevem esse texto rosiano no universo do mito.

The article aims at showing, from the reading of Guimarães Rosa’s text “Ao Pantanal”, the extent to which the presence of this Brazilian region impregnates thenarrator-protagonist, who describes the “rhapsody of perceptions” he has experiencedalong his crossing. The concretion and condensation of the language inscribe this textby Rosa in the universe of myth.
The Pantanal Wetlands Rhapsody
Keywords: Perception; Extensity; Intensity; Guimarães Rosa; Myth; Percepção; Extensidade; Intensidade; Texto rosiano; Mito